Institutional Challenges to Workforce Development in Maine - Remington, Thomas (Maine Policy Review, 2020)
The problem of workforce development in Maine has become acute. An important factor for understanding the issue of workforce development, in Maine and nationally, is rising economic inequality. High inequality impedes the working of labor markets, and over time, reduces opportunity and mobility. In Maine, as elsewhere, income gaps have widened between rich and poor while the middle class has been shrinking. Moreover, the gap between high-income and low-income counties has been growing. Meantime, many good-paying jobs are going unfilled. Comprehensive institutional solutions can help overcome these problems by matching supply and demand in the labor market, but they are not simple or cheap. Three such arrangements are described: apprenticeships; specialized wraparound programs focusing on disadvantaged or marginalized individuals; and college-and-career readiness programs aimed at secondary-level students. These solutions require effective intermediary organizations that foster sustained trust and cooperation among business, education, government, and the civic sector.
Keywords: apprenticeships; college-and-career readiness programs; wraparound programs; inequality